Disorientation of Religious Sacred Values in Religious Content on Youtube - Kuswana, Dadang; Rohendi, Leon (Asyahid Journal of Islamic and Quranic Studies (AJIQS), 2022)
Religious content on YouTube is increasingly popular and provides an opportunity for individuals and organizations to spread religious teachings and practices to a global audience. However, this platform has the potential risk of disorienting religious sacred values. This article aims to identify the factors that cause disorientation of religious sacred values in religious content on YouTube. A literature study with a qualitative approach was carried out to analyze the content of several religious contents selected purposively from YouTube. The article shows that commercialization, violence and extremism give rise to an attitude of indifference to the social and cultural context, and a lack of knowledge about religion (permissiveness) is the cause of disorientation and desacralization of religious values in religious content on YouTube. The role of producers who produce, consume and publish religious content is central in avoiding the production of religious content that has the potential to trigger conflict and tension between people of different religions. Keywords: value disorientation, religious sacredness, religious content, Youtube   Abstrak Konten keagamaan di Youtube semakin populer dan memberikan kesempatan bagi individu dan organisasi untuk menyebarkan ajaran dan praktik keagamaan pada audiens global. Namun, platform itu memiliki potensi risiko terjadinya disorientasi nilai-nilai sakralitas agama. Artikel ini bertujuan mengidentifikasi faktor-faktor yang menjadi penyebab terjadinya disorientasi nilai-nilai sakralitas agama pada konten keagamaan di Youtube. Studi literatur dengan pendekatan kualitatif dilakukan guna menganalisis konten terhadap beberapa konten keagamaan yang dipilih secara purposive dari Youtube. Dalam artikel ditunjukkan bahwa komersialisasi, kekerasan dan ekstremisme menimbulkan sikap tidak peduli terhadap konteks sosial dan budaya, dan kurangnya pengetahuan tentang agama (permisif) menjadi sebab terjadinya disorientasi dan desakralisasi nilai-nilai agama pada konten keagamaan di Youtube. Peran produsen yang memproduksi, mengonsumsi, dan memublikasikan konten-konten agama menjadi sentral posisinya dalam menghindari produksi konten-konten agama yang berpotensi memicu konflik dan ketegangan antarumat berbeda agama. Kata kunci: disorientasi nilai, sakralitas agama, konten keagamaan, Youtube